Clinical and genetic factors influencing cardiovascular risk in patients with familial hypercholesterolemia. (April 2010) - Oosterveer, Daniëëlla M; Versmissen, Jorie; Schinkel, Arend FL; Langendonk, Janneke G; Mulder, Monique; Sijbrands, Eric JG
Patients with familial hypercholesterolemia (FH) have high levels of LDL-C, owing to defective uptake of these particles by LDL receptors in the liver. Consequently, FH patients have a high risk of cardiovascular disease (CVD). However, among these patients, there is marked variance in age of onset of CVD and a proportion of untreated patients do not develop CVD at all. Statin treatment can greatly reduce risk, and since it is not yet possible to precisely predict which FH patients will develop CVD, all patients initiate treatment once the diagnosis has been made. The purpose of this article is to provide an update of clinical and genetic risk factors influencing CVD risk in FH patients, and to discuss future lines of research that could uncover improved methods of treatment for heterozygous FH patients.